(untitled) (TAJ: Journal of Teachers Association, 2018)
This study was aimed to identify risk factors of preterm LBW babies by following a cross sectional type of comparative study. This study was conducted at inpatient department of paediatrics of Rajshahi Medical College Hospital from January 2009 to December 2010. A total 150 preterm babies were included in this study. The mothers of the babies were studied to identify some selected risk factors. Maternal poor nutritional status (p<.001), low age at conception (p<.003), poor antenatal care (p<.001) and low level of education (p<.002) were found significant socio-economic risk factors. Maternal health related conditions like Antepartum haemorrhage (p<.001), Premature rupture of the membrane (p<.001), toxemia of pregnancy (p<.005), anaemia (p<.002) all were found as the significant contributors of preterm birth. This study might help to reduce the incidence of mortality and morbidity of preterm infants by providing information regarding risk factors. TAJ 2011; 24(2): 95-100